Between Sarcasm and Subtitles: The Mutability of Iraqi Satire in English Translation (المجلة الدولية للعلوم التربوية والآداب, 2025)
This paper investigates the auto-generated translation of Arabic satirical content, specifically from Iraqi Instagram and YouTube creators Amer Al-Jazie and Ahmed Albasheer, into English for global audiences. Focusing on audiovisual satire that critiques Iraqi political and social life, it explores the challenges of rendering multimodal, performative humor across languages and platforms.The study illustrates how meaning in social media satire is not only verbal but distributed across gesture, tone, editing, and visual elements. It presents two case studies: one featuring a satirical Instagram reel by Amer Al-Jazie critiquing nationalistic propaganda around women’s attire, and the other from Albasheer’s YouTube show “Nathala” highlighting translation failures in subtitled Iraqi dialect.Through critical multimodal analysis, the paper shows how literal or automated translations often flatten humor, distort political critique, or misrepresent key cultural references. These examples demonstrate the limitations of AI-based translation systems and emphasize the translator’s evolving role as a cultural mediator. The paper concludes that in digital contexts, translation must move beyond equivalence toward curatorial, context-sensitive strategies that preserve the political and ideological force of satire.